Locally nilpotent derivations and Nagata-type utomorphisms of a polynomial algebra - Bodnarchuk, Yu. V.; Prokof’ev, P. H. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study locally nilpotent derivations belonging to a Lie algebra $sa_n$ of a special affine Cremona group in connection with the root decompositions of sa n relative to the maximum standard torus. It is proved that all root locally nilpotent derivations are elementary. As a continuation of this research, we describe two- and three-root derivations. By using the results obtained by Shestakov and Umirbaev, it is shown that the exponents of almost all obtained three-root derivations are wild automorphisms of a polynomial algebra in three variables.